Abundance, species composition and daily pattern of bees visiting field bean, goat’s rue and turnip rape in southern Finland - Varis, Anna-Liisa (Agricultural and Food Science, 1995)
Visits of honeybees (Apis mellifera L.) and bumblebees (Bombas spp.) to flowers of field bean (Vida faba L.), goat’s rue (Galega orientalis Lam.) and spring turnip rape (Brassica rapa ssp. oleifera DC.) were studied to get some basic knowledge about the species composition, abundance and daily rhythm of bees visiting these plants. The studies were made under field conditions. Only pollinating specimens were counted. Both on field bean and goat’s rue 44% of the visitors were honeybees, on turnip rape the proportion of honeybees was 96%. Field bean was visited by Bombas subterraneus (L.)/B, hortorum (L.) as well as by B. lucorum (L.). These species were also present on goat’s rue; the most numerous bumblebee species on this plant, however, was B. lapidarius (L.) which was also the only bumblebee species visiting turnip rape. The total number of bees was highest on goat’s rue. The visits of honeybees began on field bean at noon and were most numerous in the afternoon. On goat’s rue, the numbers were smaller in the mornings, whereas turnip rape was visited at a rather constant rate throughout the day. On field bean, the numbers of B. subterraneus/B. hortorum increased and those of B. lucorum decreased towards the afternoon. On goat’s rue, these species were present in the morning and in the afternoon. B. lapidarius was present on goat’s rue during the whole day, but on turnip rape only in the mornings. On the basis of these results and earlier investigations it is concluded that the numbers of natural pollinators are rather low to assure adequate pollination in turnip rape and large field bean areas under the conditions in southern Finland. If the growing of goat’s rue becomes more prevalent, its pollination requirements need further studies.